Providing woman-centred care in complex pregnancy situations. (November 2021) - Naughton, Simone L.; Harvey, Clare; Baldwin, Adele
Highlights: When the philosophy of woman-centred care is not maintained, this places a woman with a complex pregnancy at risk of 'falling through the gaps' between maternity services, models of care and health providers. Professional power differentials provoke professional boundary tensions and create barriers to woman-centred care in maternity services. Organisational and siloed approaches to maternity care create barriers for midwives to provide woman-centred care. Midwifery models of care intend to push the marker on the power continuum towards autonomy giving control of childbearing experiences back to the woman. Abstract: Objective: Midwifery philosophy and practice is grounded in providing woman-centred care. The available evidence was reviewed to better understand how to provide Woman-centred midwifery care in complex pregnancy situations. Complexity in this context is defined as psychosocial or biomedical risk factors that place the mother and/or her baby at increased risk for adverse outcomes. Design: A comprehensive integrative review was undertaken to identify peer reviewed research in English over the last 5 years. The quality of the studies was assessed using the Critical Appraisal Skills Programme Tool. Setting/Participants: Published studies which discussed enablers and barriers to woman-centred care for pregnant women with complex needs. 13 papers met the inclusion criteria for this review. Findings: This review identifies that Organisational and Professional power differentials create barriers to woman-centred care and provoke professional boundary tensions. For a woman with a complex pregnancy, this places her at risk for 'falling through the gaps' between maternity services, models of care and health providers. Key conclusions: Women, birth and midwifery care are still largely constrained within a biomedical model of maternity care. Whilst barriers to woman-centred care have been identified, for women with complexity in pregnancy there appear to be few solutions when care requires multi-specialist input and crossing the boundaries and silos of healthcare.